Randomized clinical trial of a handheld cooling device (Menopod®) for relief of menopausal vasomotor symptoms. (3rd September 2015) - Reid, R. L.; Magee, B.; Trueman, J.; Hahn, P. M.; Pudwell, J.
Abstract: Objective Anecdotal reports suggest that application of a cool device to the back of the neck at the onset of a hot flush can afford symptomatic relief. The effects of a novel handheld mechanical cooling device in a population of perimenopausal women with moderate-to-severe vasomotor symptoms were evaluated. Methods In this randomized, double-blind, sham-controlled pilot study, 40 perimenopausal women experiencing ≥ 7 moderate-to-severe hot flushes per day were recruited at a single university site. Women were randomized to the active ( n = 20) or sham ( n = 20) device, which was applied to the back of the neck with each hot flush over the 4-week treatment period. Hot flush scores were calculated based on frequency and severity of symptoms. The Carpenter Hot Flash Related Daily Interference Scale and Zung Anxiety Scale were used to evaluate impact on quality of life. At study end, participants completed an open-ended questionnaire to assess the degree of unblinding and overall subjective improvement in symptoms with use of the device. Results No statistically significant differences were observed between the effects of the active and sham device. However, thematic analysis of the open-ended questionnaire revealed that 12/17 women (70.6%) in the active group, compared to 4/18 (22.2%) women in the sham group felt the device provided some symptomatic relief. Conclusions Although the majority of women using the active device acknowledged that its cooling effect afforded a degree of symptomatic relief, the symptom scores chosen for this pilot study did not reflect a beneficial effect.